Arah Pembangunan Ketahanan Keluarga Pemerintah Kota Bekasi Dalam Perspektif Kompilasi Hukum Islam - Nurfitrah, Muhammad Al Aziz; Supriyanto, Agus (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2020)
This study analyzes the direction of family resilience development from the perspective of IslamicLaw Compilation. This research is a field research, using descriptive methods with an interdisciplinaryapproach, such as the normative approach, the sociological approach and the psychologicalapproach. From the results of this study it can be concluded that Efforts to build family resilience areby improving family quality, through family development programs by increasing the role and qualityof the family. The components of family resilience are (1). Physical Resilience, related to the economiccapacity of the family. (2). Social Resilience, is the strength of the family in the application of religiousvalues, maintenance of bonds and commitment, effective communication, division and acceptance ofroles, setting goals and encouragement to progress, which will be a strength in dealing with familyproblems and having positive social relationships. (3). Psychological Resilience, The ability of familymembers to manage their emotions resulting in a positive self-concept and satisfaction with meetingneeds and achieving family development tasks. Thus a family that is not immune can be seen from theunderstanding between each family member in understanding the roles and functions as well as therights and obligations of each family member.